In vitro Condensation Assay of Fluorescent Protein-Fused PRPP Amidotransferase Purified from Budding Yeast Cells - Masak Takaine (Bio-Protocol)
De novo synthesis of purine nucleotide is essential for the production of genetic materials and cellular chemical energy. PRPP amidotransferase (PPAT) is the rate-limiting enzyme in de novo purine synthesis, thereby playing a crucial regulatory role in this pathway. Recent studies suggest that metabolic enzymes, including PPAT, form condensates through phase separation to regulate cellular metabolism in response to environmental changes. However, due to the lack of methods for purifying eukaryotic PPAT, the biophysical properties of the enzyme have remained unknown. Here, I describe a protocol for purifying budding yeast PPAT tagged with green fluorescent protein from yeast cells, as well as an in vitro assay to examine condensation of the fluorescent PPAT by microscopy. These techniques enabled us to elucidate the mechanism controlling PPAT condensation and may also be applicable to the purification and condensation assay of other enzymes.